THE ANALYSIS OF ECONOMY POTENTIAL AND BASE SECTOR OF SEVEN PROVINCES IN SUMATERA - Ukhti Ciptawaty; Neli Aida; Ahmad Dhea Pratama (Journal of Indonesian Applied Economics, 2020)
This study aims to calculate the relative ratio of the value added contribution of a sector in Sumatra region to the value added contribution of the sector concerned on a provincial or national scale growth patterns in South-Sumateran distinct groups of regions across Sumatera Island from 2014 until 2019. The analysis follows the two steps of quantitative analysis tools; Location Quotation (LQ) and Klassen Tipology.The LQ analysis will show of quantifying how concentrated a particular source of income, geographic, and the demographic group is in a region as compared to the nation. It can reveal what makes a particular region â€œuniqueâ€ in comparison to the national average. The results showed that the GDRP business sector which has high potential value and high added value significantly spurs economic growth. This article ends with several policy recommendations for lagging regions. TheÂ  recommendation and analysis will help to organize the economic growth of each province in a structured manner based on its sector potential.